2014
DOI: 10.1002/adem.201400097
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of Ceramic‐Based Materials

Abstract: This paper offers a review of present achievements in the field of processing of ceramic-based materials with complex geometry using the main additive manufacturing (AM) technologies. In AM, the geometrical design of a desired ceramic-based component is combined with the materials design. In this way, the fabrication times and the product costs of ceramic-based parts with required properties can be substantially reduced. However, dimensional accuracy and surface finish still remain crucial features in today's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
340
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 682 publications
(383 citation statements)
references
References 271 publications
1
340
0
3
Order By: Relevance
“…, where Q is the air volume in the chamber (2000 cm 3 ), h is the height (5 cm) of the specimen (Fig. 3a), S is the specimen cross sectional area (19.63 cm 2 ), and t the passage time for the 2000 cm 3 of air (in minutes).…”
Section: Specimen Characterizationmentioning
confidence: 99%
“…, where Q is the air volume in the chamber (2000 cm 3 ), h is the height (5 cm) of the specimen (Fig. 3a), S is the specimen cross sectional area (19.63 cm 2 ), and t the passage time for the 2000 cm 3 of air (in minutes).…”
Section: Specimen Characterizationmentioning
confidence: 99%
“…Different 3D printing processes have been developed for different materials. Modern devices can utilize polymers, metals, ceramic, and even bio-materials for printing human tissues, e.g., [141], [139], [42]. Due to the fast development of the technology, cheap desktop 3D printers are widely available for both prototyping, as well as mass production.…”
Section: Length Scale In Macro Scale Production Processesmentioning
confidence: 99%
“…Numerous authors have reported the fabrication of porous scaffolds by 3DP (Bose et al 2013, Travitzky et al 2014. Pure CaP powders, for example α-and β-tricalcium phosphate (TCP) (Butscher et al 2012), tetracalcium phosphate (Khalyfa et al 2007), and HA as well as composites of CaPs mixed with organic polymers, such as poly(L-lactide-co-glycolide)-copolymer (PLGA) , have been utilised as stock materials.…”
Section: Physical Challengesmentioning
confidence: 99%